(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
Among the Unified Power Flow Controller (UPFC) tools, Flexible Alternating Current Transmission Systems (FACTS) have ability to control the transmitted power, improve transient and dynamic stability and improve the profile of the voltage and damping of the oscillations in the power system. Using the proportional-integral (PI) and proportional-integral-derivative (PID) controllers is a custom method. Selecting the PI and PID coefficients is through different methods. Also designing a resistant controller which can control the system in different points of work has been continuously considered by researchers. In this regard, in order to improve the performance of UPFC controllers, adjusting its parameters is required optimally which this matter itself would facilitate accessing to control objectives. In this project, UPFC is used for damping the oscillations of the power system. Also, in order to adjust the controller parameters optimally, evolutionary algorithms like Ant Colony Optimization (ACO), Particle Swarm Optimization (PSO), Hybrid Particle Swarm Optimization (HPSO) and other algorithms are used. Bangladesh J. Sci. Ind. Res. 51(3), 231-238, 2016